KESEIMBANGAN BAHASAN FIQIH MUAMALAH DAN AKUNTANSI SYARIAH BAGI SISWA SMKN 201 JAKARTA - Krisno Septyan; Wisnu Julianto (LPPM UPN Veteran Jakarta, 2018)
The school vocational has been programing by government to create graduates whose ready to work,however thats goal not only oriented on result, but also oriented on processing. Fiqih mumalah can be acomodated proses and result to be a bless god. Gradutate can get result (salaries) but not disregard etich. In another goal this program is support our research. Processing method this our program are give discussions fiqih muamalah and financial statement for islamic institutition with hooking in daily activities, than answer question session. Result this program is student’s got understanding of all about transaction which no contradict in islamic rule and we can seem student’s awareness to muamalah is so much. This moment is support get learning outcomes is pious to God.